Investigation of the Differences in Onset Times for Magnetically Conjugate Magnetometers - Weygand, James M.; Zesta, Eftyhia; Kadokura, Akira; Oliveira, Denny M. (Frontiers in Astronomy and Space Sciences, 2022)
We have identified nearly 1000 onsets using two pairs of hemispherically conjugate ground magnetometers where the onset is defined based on a sharp decline in the H component of the magnetic field at a ground magnetometer station. Specifically, we used the pair of stations at West Antarctica Ice Sheet Divide and Sanikiluaq, Canada plus Syowa, Antarctica and Tjörnes, Iceland. While the onset times in the southern hemisphere is identified by eye, the value of the differences in the onset time between the northern and southern hemispheres are determined using cross covariance. We observe differences in the onset time between the two hemispheres as large as several minutes, but 53% of the events show no difference in the onset time. Using statistics we show that the largest differences in onset time are associated with the summer and winter seasons and when the IMF By value is limited between 0.5 and 2.5 nT, which is the IMF By range when the local time difference between the northern and southern hemisphere foot points is the smallest. The results indicate that ionospheric conductivity associated with solar illumination plays a role in the differences in onset time between the northern and southern hemisphere when only non-zero differences in onset time are considered. We validate these results with two other less robust methods. The median value of the differences in onset time indicates the onsets occur ~23 s earlier in the winter hemisphere than in the summer hemisphere. It has been reported that the time difference between the start of the substorm in the magnetotail and the observed auroral break up (substorm auroral onset) in the ionosphere is 30 s to 2 min in the current disruption model and the near earth neutral line model, respectively. Our results may be of interest to those two models.